Prediction of Evaporator Performance of Double Effect Steam Absorption Chiller - Noor Azman, Muhammad Aiman Faris (2018)
Generation of chilled water mostly done using absorption chillers in cooling plant. The application of double effect type chillers are normally be used as it can offer high efficiency compared to single-effect chillers. The COP double-type varies between 0.7 to 1.3. The relation of internal heat input could give effect to the COP of the chillers. This study was related to the evaluating COP changes with increasing of evaporator performance by using internal operating condition of double effect steam absorption chiller. Operating data for 61 days were used for the study. Duhring double effect schematic diagram was used for developing mass and energy balance equations. Results demonstrated actual COPs were between 1.3 to 1.5 and trends increased simultaneously to the incremental of evaporator performance. From COP outcomes obtained, the results were found to be within the range of COP from other researchers. Due to uncertainty in chiller machine performance, it is recommended to perform economic analysis so that decision can be made whether to replace or keep up the existing absorption chiller.